Lessons of Krapivna - Tokarev, Nikita (project baikal, 2015)
Based on the example of the graduation project concerning the town Krapivna, that was worked out by the MARCHI Experimental Design Studio in 2010, the author features the problems of architectural education and the educational mechanisms that will contribute to professional formation of future architects.
Keywords: architectural education; research project; involvement; contact with life; Solovki